(untitled) (Pedagogy of Higher and Secondary Education, 2011)
In the article the state of research of problem of preparation of senior pupils to the pedagogical profession in the psychologically-pedagogical science and practice, and possibilities of its decision are determined in the conditions of profile studies of senior pupils are analyzed by the author.